Formulasi dan Evaluasi Tablet dengan Bahan Tambahan Tongkol Jagung (Zea mays L.) sebagai pengganti HPMC yang digunakan untuk Anti Diabetes - Surbakti, Christica Ilsanna; Suryani , Monica; Nerdy, Nerdy (Journal of Pharmaceutical and Sciences, 2025)
Corn (Zea mays L) is a food crop that is known and cultivated in developing countries. So far, corn cobs have not been widely used as a value-added product. Corn cobs have 35.5% crude fiber, 2.5% protein, 0.12% calcium, 0.04% phosphorus and the remaining 38.16% of other substances. Corn cobs, which are biomass, contain phenolic phytochemicals which are very likely to be used as active antioxidant ingredients. The choice of method for making tablets is adjusted to the characteristics of the active substance used. In this research, the method used in making metformin HCl tablets was wet granulation. Wet granulation is the process of adding liquid to a powder or powder mixture in a container equipped with stirring which will produce agglomeration or granules. The evaluation results of corn cob additive granules as a substitute for HPMC showed the results of the flow time test (F1 1.5 seconds, F2 1.4 seconds F3 1.63 seconds), F1 angle of repose test (34.96 o, F2 41, 43 o, F3 41.92 o), humidity test (F1 1.794 %, F2 1.999 %, F3 2.331 %) and compressibility test (F1 11 %, F2 15%, F3 8%).  The results of the evaluation of antalgin tablets using corn cobs as a substitute for HPMC showed visual test results where the tablets were round and white in color, the weight uniformity test showed results (F1 A (5%) 708.7-783.3 and column B (10% ) 671.4-820.6, F2 A (5%) 562.775– 705.75 and column B (10%) 571.05-698.6, F3 688.75– 761.25 and column B (10%) 625.5-797.5), size uniformity test shows results (F1 diameter 1.3545 and thickness 0.4705, F2 diameter 1.359 and thickness 0.468, F3 diameter 1.36 and thickness 0.471), fragility test shows results (F1 0 .06978367 %, F2 0.53272451 %, F3 0.06978367 %) and tablet hardness showed results (F1 6.764, F2 4.984, F3 7.89) and disintegration time test showed results (F1 2 minutes, F2 2 minutes, F3 2 minute).